2021
DOI: 10.3390/plants11010024
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Plant Leaves Using New Compact Convolutional Neural Network Models

Abstract: Precision crop safety relies on automated systems for detecting and classifying plants. This work proposes the detection and classification of nine species of plants of the PlantVillage dataset using the proposed developed compact convolutional neural networks and AlexNet with transfer learning. The models are trained using plant leaf data with different data augmentations. The data augmentation shows a significant improvement in classification accuracy. The proposed models are also used for the classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
(69 reference statements)
0
23
1
2
Order By: Relevance
“…To enhance the VGG-19 model, they incorporated the inception module, which resulted in an improved performance. In [28], Wagle et al suggested a compact CNNbased framework for leaf infection classification. Their compact CNN-based architecture utilized "Rectified Linear Unit" ReLu [46] activation functions throughout the network and fully connected layer before making a final prediction, which increased the total training parameters and overall model complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the VGG-19 model, they incorporated the inception module, which resulted in an improved performance. In [28], Wagle et al suggested a compact CNNbased framework for leaf infection classification. Their compact CNN-based architecture utilized "Rectified Linear Unit" ReLu [46] activation functions throughout the network and fully connected layer before making a final prediction, which increased the total training parameters and overall model complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, with the advent of domain-specific architectures [18] (i.e., GPU, TPU, etc. ), deep learning (DL)-based classifiers, particularly CNN, are becoming increasingly popular [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. A CNN-based classifier (i.e., VGG-Net [34], ImageNet [35], Inception-Net [36], DenseNet-121 [37], MobileNet [38], ResNet50 [39], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy rate of the study using Flavia data was 93.82%. Wagle et al [32] designed a compact CNN with different convolutional layers, named N1, N2, and N3, for plant species classification. They tested this compact CNN model on the PlantVillage and Flavia datasets.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, convolutional-neural-network-based (CNN) deep learning approaches have rapidly developed. Compared with conventional methods, CNNs extract different levels of features from input images, achieving accurate target detection through information classification and location regression [ 30 , 31 ]. The well-known CNN architectures, such as AlexNet, ResNet50, and VGG16, can be utilized for the classification and diagnosis of diseases as well as the quality inspection of fruits and vegetables [ 32 , 33 , 34 , 35 ].…”
Section: Related Workmentioning
confidence: 99%